2010
DOI: 10.1186/bcr2633
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of biomarker selection and clinico-pathological covariate inclusion in breast cancer prognostic models

Abstract: IntroductionMulti-marker molecular assays have impacted management of early stage breast cancer, facilitating adjuvant chemotherapy decisions. We generated prognostic models that incorporate protein-based molecular markers and clinico-pathological variables to improve survival prediction.MethodsWe used a quantitative immunofluorescence method to study protein expression of 14 markers included in the Oncotype DX™ assay on a 638 breast cancer patient cohort with 15-year follow-up. We performed cross-validation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Since the beginning of the century, much of the research has been focused on issues related to personalized or stratified medicine with the assessment of genetic markers and analyses of high dimensional data as the challenge for researchers in many disciplines. A substantial part of such studies investigates issues for patients with cancer, breast cancer thereby being the disease considered most often [ 5 11 ]. Unfortunately, most of the results from the very large number of individual studies have not been validated and the number of clinically useful markers is pitifully small [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the beginning of the century, much of the research has been focused on issues related to personalized or stratified medicine with the assessment of genetic markers and analyses of high dimensional data as the challenge for researchers in many disciplines. A substantial part of such studies investigates issues for patients with cancer, breast cancer thereby being the disease considered most often [ 5 11 ]. Unfortunately, most of the results from the very large number of individual studies have not been validated and the number of clinically useful markers is pitifully small [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For some years it has been discussed to improve prediction rules through the integration of clinical and gene expression data [ 5 , 16 20 ]. However, applying combined prediction rules at a broader level would cause difficulties in many (smaller) centers and increase costs.…”
Section: Introductionmentioning
confidence: 99%
“…If the variables in Net-score are highly correlated with each other, it will cause multicollinearity problem. For example, Nottingham prognostic index (NPI), which includes tumor size, lymph node status and histological grade information, and tumor stage are well-known prognostic factor for breast cancer, however, they were not selected in the current study [ 23 , 24 ]. NPI or tumor stage has high correlation coefficients with tumor size ( Supplementary Figure 2 , NPI-tumor size: 0.55, tumor stage-tumor size: 0.48 calculated by spearman correlation or Point-Biserial correlation respectively).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that measuring bcl-2 expression in tumor biopsies was an independent predictor of breast cancer outcomes and could be useful as a prognostic adjunct to NPI, particularly in the first 5 years after diagnosis. Parisi et al [ 28 ] outlined the benefits of the inclusion of biomarkers with clinico-pathological covariate in breast prognostic models. They examined the expression of 14 biomarkers out of the 21 present in the Oncotype Dx test (Genomic Health) in addition to tumor characteristics found in NPI.…”
Section: Discussionmentioning
confidence: 99%